International financial management - Eun, Cheol S. (McGraw-Hill/Irwin, 2007)
International Financial Management combines the fundamental concepts of international finance with solid practical applications. This combination has made it the book of choice at a variety of institutions, including top business schools such as Wharton, Stanford, Northwestern, and INSEAD. Neither superficial nor overly theoretical, Eun and Resnick's approach offers a conceptually solid, yet still relevant, treatment of international financial topics that puts students on the right track to becoming effective global financial managers